Axl Promotes Zika Virus Entry and Modulates the Antiviral State of Human Sertoli Cells - Daniel P. Strange (American Society for Microbiology, 2019)
ABSTRACT Zika virus (ZIKV) is unique among mosquito-borne flaviviruses in its ability to be sexually transmitted. Persistent ZIKV infection in the testes, which are immune privileged organs, long after peripheral clearance suggests involvement of immunosuppressive pathways; however, the underlying mechanisms remain undetermined. We recently demonstrated that ZIKV infects human Sertoli cells (SC), the major cell type of the seminiferous epithelium responsible for maintaining the immune privileged compartment of seminiferous tubules. Recent reports have identified the TAM (Tyro3, Axl, Mer) receptor tyrosine kinase Axl as an entry receptor and/or immune modulator for ZIKV in a cell type-specific manner. Interestingly, the seminiferous epithelium exhibits high basal expression of the Axl receptor where it is involved in clearance of apoptotic germ cells and immunosuppression. Here, we show that Axl was highly expressed in SC compared to Leydig cells (LC) that correlated with robust ZIKV infection of SC, but not LC. Further, neutralization of Axl receptor and its ligand Gas6 strongly attenuated virus entry in SC. However, inhibition of Axl kinase did not affect ZIKV entry but instead led to decreased protein levels of suppressor of cytokine signaling 1 (SOCS1) and SOCS3, increased expression of interferon-stimulated genes (ISGs), and reduced ZIKV replication. Similarly, treatment of multicellular human testicular organoids with an Axl kinase inhibitor attenuated ZIKV replication and increased ISG expression. Together, our data demonstrate that Axl promotes ZIKV entry and negatively regulates the antiviral state of SC to augment ZIKV infection of the testes and provides new insights into testis antiviral immunity and ZIKV persistence. IMPORTANCE Recent Zika virus (ZIKV) outbreaks have identified sexual transmission as a new route of disease spread not reported for other flaviviruses. ZIKV crosses the blood-testis barrier and establishes infection in seminiferous tubules, the site for spermatozoa development. Currently, there are no therapies to treat ZIKV infection, and the immune mechanisms underlying testicular persistence are unclear. We found that multiple human testicular cell types, except Leydig cells, support ZIKV infection. Axl receptor, which plays a pivotal role in maintaining the immunosuppressive milieu of the testis, is highly expressed in Sertoli cells and augments ZIKV infection by promoting virus entry and negatively regulating the antiviral state. By using testicular organoids, we further describe the antiviral role of Axl inhibition. The significance of our research lies in defining cross talk between Axl and type I interferon signaling as an essential mechanism of immune control that can inform therapeutic efforts to clear ZIKV from the testis.